The Power of Digital Platforms in Tourism: A Communication Strategy Analysis - Maravilla, Wes Harven Guillemer (Future Science / FSH-PH Publications, 2025)
The study investigates the impact of digital platforms on English purposive communication in the tourism sector. The study employed semi-structured interviews among tourism practitioners in Boracay, Philippines, which contrasted the strategies on online engagement through different digital platforms. Key findings indicate that digital platforms have changed the communications landscape in terms of the tools to book directly, the scope to market oneself through social media and how efficiency in communications can be increased. These advances also encourage the expansion of the tourism by encouraging competitive customer interaction, easy market access and smooth transactions. The research also highlights some challenges that the tourism businesses face, such as how to handle negative online comments, the demand to keep faster pace of change in the digital world, difficulties related to languages and time zones. The study highlights the strategic role played by the digital platforms and good purposive communication in English language for fostering the growth of tourism.